Effect of short-term warming and drought on the methanogenic communities in degraded peatlands in Zoige Plateau - Li, Wei; Shi, Rui; Yuan, Lingchen; Lan, Xianli; Feng, Defeng; Chen, Huai (Frontiers in Microbiology, 2022)
Peatlands in Qinghai-Tibetan are degrading with climate change and human activities. Peatland degradation and climate change affect methane emissions. Methanogens are key functional microbes during methane production; however, knowledge on methanogens in degraded peatlands is lacking. Here, we investigated the effects of short-term (one year) warming (OTC), drought (20 %) and their combination on methanogens in the degraded peatlands on the Zoige Plateau of China via qPCR and clone library analysis. The results showed that Methanomicrobiales and Methanobacteriales were predominant in all the treatments. NMDS and PERMANOVA analyses showed that the methanogenic community structure among the climate change treatments were not significant different. The relative abundance of methanogen communities showed insignificant variation among the climate change treatments. The copy number and Shannon diversity of methanogens were significantly different within the climate change treatments, and drought significantly decreased the copy number of methanogens when compared to the control. The RDA results and correlation analysis showed that environmental variables measured had no significant effect on methanogenic community structure and Shannon diversity. These results indicate that methanogens are insensitive to short-term climate change in degraded peatlands. This study provides insight into methane emissions from the Zoige Plateau peatlands by focusing on the possible responses of the methanogens to climate-driven changes.